Multiply and simplify: (3x – 7)(-3x2 + 4x + 1)

Question

Asked 3/15/2013 12:17:36 PM

Updated 6/27/2014 10:50:32 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

amreen|Points 461|

Question

Asked 3/15/2013 12:17:36 PM

Updated 6/27/2014 10:50:32 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Rating

3

(3x – 7)(-3x^2 + 4x + 1)

=-9x^3+12x^2+3x+21x^2-28x 7

=-9x^3+33x^2-25x-7

=-9x^3+12x^2+3x+21x^2-28x 7

=-9x^3+33x^2-25x-7

Added 6/27/2014 10:50:31 AM

This answer has been confirmed as correct and helpful.

Simplify: (3.22 x 103)(4.1 x 108) User: (3.22 x 103)(4.1 x 108) User:
7t2 – 9t3 – 3t4 – 2t + 2

Question

Not Answered

Updated 3/31/2014 8:34:30 PM

1 Answer/Comment

Simplify: (x4 + 5x -3) – (5x4 – x + 2) **Weegy:** The answer for(x4 + 5x -3) – (5x4 – x + 2) is -4 x^4+6 x-5 (More)

Question

Expert Answered

Updated 7/31/2014 4:01:54 PM

0 Answers/Comments

Multiply and simplify: (2x + 7)(x – 3) **Weegy:** 16x^3 is the answer. (More)

Question

Expert Answered

Updated 6/27/2014 10:52:05 AM

1 Answer/Comment

(2x + 7)(x - 3)

=2x^2-6x+7x-21

=2x^2+x-21

=2x^2-6x+7x-21

=2x^2+x-21

Added 6/27/2014 10:52:05 AM

This answer has been confirmed as correct and helpful.

Multiply and simplify: (3m – 7)(4m – 2)

Question

Expert Answered

Updated 6/27/2014 10:51:27 AM

1 Answer/Comment

(3m - 7)(4m - 2)

=12m^2-6m-28m+14

=12m^2-34m+14

=12m^2-6m-28m+14

=12m^2-34m+14

Added 6/27/2014 10:51:26 AM

This answer has been confirmed as correct and helpful.

Multiply and simplify: (9x + 1)(x + 2)

Question

Expert Answered

Updated 6/27/2014 10:53:03 AM

1 Answer/Comment

(9x+1)(x+2)

=9x^2+18x+x+2

=9x^2+19x+2

=9x^2+18x+x+2

=9x^2+19x+2

Added 6/27/2014 10:53:02 AM

This answer has been confirmed as correct and helpful.

27,106,396

questions answered

There are no comments.